1998
DOI: 10.1002/(sici)1097-0177(199805)212:1<49::aid-aja5>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

G1-phase regulators,cyclin D1, cyclin D2, andcyclin D3: Up-regulation at gastrulation and dynamic expression during neurulation

Abstract: Gastrulation in rodents is associated with an increase in the rate of growth and with the start of differentiation within the embryo proper. In an effort to understand the role played by the cell cycle control in these processes, expression of cyclin D1, D2, and D3-three major positive regulators of the G1/S transitionhas been investigated by in situ hybrization and RT-PCR. Cyclin D1 and D2 transcripts are first detected in the epiblast at gastrulation, when a proliferative burst occurs, and subsequently in it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
68
0
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(78 citation statements)
references
References 42 publications
9
68
0
1
Order By: Relevance
“…However, in mouse embryo and some organs of adult animals, different cyclin D shows distinct expression patterns, indicating individual cyclin D may have their specific functions. In the early stage of embryogenesis, cyclin D1 and cyclin D2 display opposite and specific expression patterns in the developing hindbrain (Wianny et al, 1998). Furthermore, this exclusive expression pattern of cyclin Ds is also preserved in some organs of adult animals (Ravnik et al, 1995;Robker and Richards, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in mouse embryo and some organs of adult animals, different cyclin D shows distinct expression patterns, indicating individual cyclin D may have their specific functions. In the early stage of embryogenesis, cyclin D1 and cyclin D2 display opposite and specific expression patterns in the developing hindbrain (Wianny et al, 1998). Furthermore, this exclusive expression pattern of cyclin Ds is also preserved in some organs of adult animals (Ravnik et al, 1995;Robker and Richards, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…There is functional redundancy among these cyclin Ds, as it has been shown that cyclin D2 could substitute the function of cyclin D1 in mouse development (Carthon et al, 2005). However, each cyclin D may also have distinct functions as they are often expressed mutually exclusively in different cell types (Wianny et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Cyclin Ds are key regulators during the G1 phase and there are three types of cyclin Ds, D1, D2 and D3 in mammalian cells [3]. Although the phenotypic analyses of single cyclin D knockout mice revealed that each of the D type cyclins is sufficient to drive normal development of the majority of tissues [4], each cyclin D shows distinct and mutually exclusive expression patterns in mouse embryos and some organs of adult animals, indicating individual cyclin D may have their specific functions [5].…”
Section: Npgmentioning
confidence: 99%
“…Cyclin Ds are key regulators during the G1 phase and there are three types of cyclin Ds, D1, D2 and D3 in mammalian cells [3]. Although the phenotypic analyses of single cyclin D knockout mice revealed that each of the D type cyclins is sufficient to drive normal development of the majority of tissues [4], each cyclin D shows distinct and mutually exclusive expression patterns in mouse embryos and some organs of adult animals, indicating individual cyclin D may have their specific functions [5].It has been documented that cyclin D1 is an important target of PTEN, which downregulates the expression and protein stability of cyclin D1 and inhibits its nuclear localization [6]. PTEN also reduces cyclin D3 levels in endometrial carcinoma cells [7].…”
mentioning
confidence: 99%
“…In embryonic stem cells, the cyclin-CDK complexes (Cyclin Dependent Kinase) are constantly active and require no adjustment. The regulation of G1 phase mediated by the RB pathway is required only during differentiation (Savatieret al 1996;Wianny et al 1998;Sherr and Roberts 1995). The high proliferative rate of embryonic stem cells is also due to the fact that the cell cycle progression is independent from the action of mitogenic factors, such as the Ras/ERK pathway (Burdon et al 1999;Jirmanova et al 2002;Schratt et al 2001).…”
Section: Figure 2 Cardiogenic Pathwaysmentioning
confidence: 99%